Regulating Public Relations: How U.S. Legal Policies and Regulations Shaped Early Corporate Public Relations. Issue 2 (2nd April 2020) - Myers, Cayce
Abstract : Nineteenth and twentieth century developments in corporations' legal duties involving "public relations" activities gave rise to professional public relations practice. During the nineteenth and early twentieth centuries, court cases, trade press, and the popular press used the term "public relations" to refer to the status of an organization and certain expected behaviors. As corporations and utilities grew in the late nineteenth century these "public relations" responsibilities were applied to them creating a legal requirement of transparency, disclosure, and good faith actions. Examining court decisions and the popular press this paper shows how this application of the term "public relations" to corporations had a relationship with public relations practice. Implications for public relations historiography and American public relations development are discussed.